The Development Strategy of Soybean Agribusiness in PT Lentera Panen Mandiri - Dewi Nurpitasari; Lestari Rahayu Waluyati; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2018)
The aims of this study are to identify both internal and external factors of agribusiness in PT Lentera Panen Mandiri (PT LPM), map the company’s position, and determine its development strategy. Main data used in this study is primary data obtained from stakeholders of PT LPM by direct interview. Strength, Weakness, Opportunity and Threat (SWOT) of soybean agribusiness in PT LPM were identified in this study and followed by determining the company’s position using SWOT diagram. Alternative srategies were derived from the SWOT matrix and prioritized using Quantitative Strategies Planning Matrix (QSPM) analysis. The results of this study identified 5 strengths, 7 weaknesses, 9 opportunities, and 6 threaths with the highest factors consisted as